2021
DOI: 10.1038/s41559-020-01388-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic signatures of coral bleaching history

Abstract: Coral bleaching, a process where corals expel their photosynthetic symbionts, has a profound impact on the health and function of coral reefs. As global ocean temperatures continue to rise, bleaching poses the greatest threat to coral reef ecosystems. Here, untargeted metabolomics was used to analyze the biochemicals in pairs of adjacent corals from a patch reef in Kāneʻohe Bay, Hawaiʻi, where one colony in the pair bleached (in 2015) and recovered while the other did not bleach. There was a strong metabolomic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 54 publications
1
71
1
Order By: Relevance
“…In the context of repeat bleaching, the slower recovery of M. capitata than P. compressa from bleaching observed throughout Kaneohe Bay in 2015 (Matsuda et al, 2020; Ritson‐Williams & Gates, 2020) likely meant that bleaching‐susceptible M. capitata was in worse energetic standing than P. compressa going into the following event in 2019 and thus was more susceptible to severe bleaching despite lower levels of heat stress in the second event. Indeed, even 4 years following the 2015 bleaching event, bleaching‐susceptible colonies of M. capitata had distinct lipid profiles from bleaching‐resistant colonies despite both phenotypes appearing visually healthy (Roach et al, 2021), supporting the hypothesis that recovery prior to the 2019 event was incomplete in this species. A slow energetic recovery has been shown to make individuals less resistant to bleaching and mortality following repeat exposure to heat stress in other coral species (Sale et al, 2019), highlighting a barrier to acclimatization and the uneven harm of repeat bleaching on different coral species.…”
Section: Discussionmentioning
confidence: 86%
“…In the context of repeat bleaching, the slower recovery of M. capitata than P. compressa from bleaching observed throughout Kaneohe Bay in 2015 (Matsuda et al, 2020; Ritson‐Williams & Gates, 2020) likely meant that bleaching‐susceptible M. capitata was in worse energetic standing than P. compressa going into the following event in 2019 and thus was more susceptible to severe bleaching despite lower levels of heat stress in the second event. Indeed, even 4 years following the 2015 bleaching event, bleaching‐susceptible colonies of M. capitata had distinct lipid profiles from bleaching‐resistant colonies despite both phenotypes appearing visually healthy (Roach et al, 2021), supporting the hypothesis that recovery prior to the 2019 event was incomplete in this species. A slow energetic recovery has been shown to make individuals less resistant to bleaching and mortality following repeat exposure to heat stress in other coral species (Sale et al, 2019), highlighting a barrier to acclimatization and the uneven harm of repeat bleaching on different coral species.…”
Section: Discussionmentioning
confidence: 86%
“…The betaine lipids have been previously reported in endosymbionts from various coral species (Rosset et al, 2019;Sikorskaya, 2020;Sikorskaya et al, 2021) and are reported as biomarkers of bleaching history (Roach et al, 2021) and thermal tolerance (Leblond et al, 2015;Rosset et al, 2019). It has been previously suggested that betaine lipids being the component of cell membrane are influenced by the host genotype (Sikorskaya et al, 2021).…”
Section: Resultsmentioning
confidence: 96%
“…Requires molecular work, may be transient, some species do not harbor diverse assemblages Potentially scalable, well-studied system, predictable tradeoffs Rowan, 2004;Berkelmans and van Oppen, 2006;Sampayo et al, 2008;Cantin et al, 2009;Cunning et al, 2016 Barshis et al, 2010;Innis et al, 2018;Mayfield et al, 2018;Majerova et al, 2020*;Williams et al, 2020*;Majerova and Drury, 2021*;Roach et al, 2021 *Indicates pre-prints available online.…”
Section: Trade-offs In Proactive Coral Reef Restorationmentioning
confidence: 99%